(untitled) (Plant Tissue Culture and Biotechnology, 2010)
In an effort to improve salinity tolerance in rice, the Pennisetum glaucum vacuolar Na+/H+ antiporter gene (PgNHX1) was transformed and expressed in Bangla-deshi rice Binnatoa under the constitutive promoter CaMV35S. Transgenic status of the plant was confirmed by PCR and Southern blot hybridization. RT-PCR and Western dot-blot analyses were performed to validate the expression of the transgene at RNA and protein levels, respectively. At 160 mM (ECe of 16 dS/m) NaCl stress the transgenic seedlings showed enhanced tolerance compared to controls. Key words: Salinity tolerance, PgNHX1, CaMV35S, Binnatoa D.O.I.10.3329/ptcb.v19i1.4912 Plant Tissue Cult. & Biotech. 19(1): 25-33, 2009 (June)